THE INFLUENCE OF SOCIAL CLASS AND LIFESTYLE ON CONSUMER BEHAVIOR OF SUZUYA MALL BIREUEN - Riska Maulida; Arini Rusydi; Anis Ulfa; Bunnaia; Ivvon Septina Bella (Universitas Efarina, 2024)
This research aims to determine the influence of social class and lifestyle on consumer behavior at Suzuya Mall Bireuen. The population used in this research was 96 people, the sample used was accidental sampling. The data analysis method used in this research is multiple linear regression analysis using the SPSS version 25 program and Microsoft Excel 2016. Based on the research results, it is known that partially, the social class variable has a significant effect on consumer behavior with a sig value of 0.000 < 0.05. Lifestyle variables also have a significant effect on the sig value. 0.013 < 0.05. Meanwhile, simultaneously the social class variable and lifestyle variable have a significant influence on consumer behavior with a sig. 0.000 < 0.05. The R Square value for consumer behavior at Suzuya Mall Bireuen is 0.969. This means 96.9%. Variations in consumer behavior are influenced by social class and lifestyle and the remaining 3.1% is determined by other variables outside the contribution of this research.